Response to extreme energy price changes: Evidence from Ukraine - Anna Alberini; Olha Khymych; Milan Scasny (ETH Zurich, CER-ETH - Center of Economic Research, 2017)
Large but temporary price increases are sometimes deployed on days when the demand for electricity is extremely high due to exceptionally warm or cold weather. But what happens when the extreme price changes are permanent? Between January 2013 and April 2016, natural gas and electricity prices in Ukraine increased dramatically (up to 300% of the initial rates). We exploit variation in tariffs over time and across customers to estimate the price elasticity of electricity demand using a panel dataset with monthly meter readings from households in the city of Uzhhorod in Ukraine. We ask three research questions. First, what is the price elasticity of consumption implicit in the response (if any) to these large electricity price changes? Second, is there evidence of heterogeneity in the price elasticity of electricity demand driven by dwelling or household characteristics, or by consumer understanding of block pricing and/or own consumption levels? Third, how quickly do household adjust their consumption after a price change? Histograms of the monthly usage records suggest that our Ukrainian consumers were aware of the increasing block pricing system and responded to marginal prices, with bunching observed at the then-current as well as future block cutoffs. The price elasticity of electricity demand is approximately -0.2 to -0.5, with the bulk of our estimates around -0.3. The elasticity becomes up to 50% more pronounced over the first three months since prices change. We find only limited evidence that persons who are attentive about their consumption levels, their bills, or the tariffs are more responsive to the price changes. The tariff increases do help reduce CO2 emissions, but at a high cost per ton.
Keywords: Q41; Q48; Q54; 330; residential electricity demand; short-run price elasticity; increasing block rates; attentiveness; CO2 emissions reductions